Mercury removal from gold mining wastewater using palm oil fuel ash (POFA) - Rainiyati Rainiyati; Ahmad Riduan; Sarah Fiebrina Heraningsih; Bunga Andari Mukhtasida (Brawijaya University, 2022)
Mercury is a harmful element that commonly accumulates in the environment through anthropogenic activities such as gold mining. This study aimed to examine the use of palm oil fuel ash (POFA) as an agricultural waste to remove mercury in gold mining wastewater. The technology applied in this study was adsorption and precipitation. POFA was first washed until neutral then mixed with gold mining effluent with time variation of 30, 60, 90 minutes. Next, precipitate it for 30 minutes. The adsorbent dose used in this study was 250 mg with 1 litre effluent. The maximum adsorption efficiency observed in this study was 96.77%. The utilization of POFA as an adsorbent reduced mercury levels in wastewater below the allowed released mercury level to the environment (0.0025 mg Hg/L). Results indicate that reducing mercury from gold mining wastewater by utilizing POFA was simple, effective, and low-cost to be implemented.